Association between out-of-pocket expenditure and health-related quality of life among patients receiving cancer treatment: a cross-sectional study from Nepal - Pratik Khanal; Suman Sapkota; Nirmal Poudel; Achyut Raj Pandey; Bidwata Bhattarai; Etna Khatiwada; Ravi Kant Mishra; Biraj Man Karmacharya; Shiva Raj Adhikari; Kjell Arne Johansson; Krishna Kumar Aryal (Health and Quality of Life Outcomes)
Abstract Background The financial burden of cancer care may significantly impair patients’ health-related quality of life (HRQoL), yet the extent and nature of this relationship remain underexplored, particularly in low-resource settings. This study aimed to report the HRQoL of patients currently receiving treatment for selected cancers (breast, cervical, lung, oesophageal and stomach) in Nepal. We further investigate the association of out-of-pocket expenditure (OOPE) with HRQoL. Methods A cross-sectional survey was conducted from April to May 2024 among 353 patients undergoing cancer treatment in two tertiary cancer hospitals in Nepal. We used the European Quality of Life 5 dimensions (EQ-5D-5L) and the European Quality of Life Visual Analogue Scale (EQ-VAS) to obtain their HRQoL. Similarly, we collected sociodemographic and treatment-related data, including OOPE and patient satisfaction. We used the ordinary least squares estimation with robust standard errors to identify the association between OOPE and HRQoL (EQ-5D-5L index score). Results The mean (SD) EQ-5D-5L index score was 0.39 (0.42), and the mean (SD) EQ-VAS score was 56.65 (21.71). Anxiety/depression and pain/discomfort were the most common reported problems (> 90% of the study participants), whereas pain/discomfort had the greatest disability weight (0.17). In the regression analysis, the logarithms of OOPE (β = -0.086; 95% CI: -0.132 to -0.040) was significantly associated with a lower EQ-5D-5L index score. Other significant covariates included being currently not married (β = -0.149; 95% CI: -0.274 to -0.024), having stage IV cancer during diagnosis (β = -0.212; 95% CI: -0.364 to -0.061) and patient satisfaction score (β = 0.015; 95% CI: 0.001 to 0.030). Conclusions The study revealed a moderate quality of life among patients currently receiving cancer treatment in Nepal. Higher OOPE along with stage IV cancer during diagnosis and being currently not married were associated with lower HRQoL, whereas higher patient satisfaction score was associated with higher HRQoL. These insights might be helpful for providing targeted interventions such as emphasizing early diagnosis and management and focusing on patient satisfaction and those at financial risk to improve the HRQoL of people with cancer.